2022
DOI: 10.3390/s22155642
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Examining the Effects of Music Training on Attention in Children with Fetal Alcohol Spectrum Disorders (FASD)

Abstract: Prior studies indicate differences in brain volume and neurophysiological responses of musicians relative to non-musicians. These differences are observed in the sensory, motor, parietal, and frontal cortex. Children with a fetal alcohol spectrum disorder (FASD) experience deficits in auditory, motor, and executive function domains. Therefore, we hypothesized that short-term music training in children with an FASD due to prenatal alcohol exposure may improve brain function. Children (N = 20) with an FASD were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Art therapies can also improve brain function and serve as a valuable method for planning complex care in FASDs. A pilot study examining the effects of music training on attention in children with FASDs showed promising results [48].…”
Section: Discussionmentioning
confidence: 99%
“…Art therapies can also improve brain function and serve as a valuable method for planning complex care in FASDs. A pilot study examining the effects of music training on attention in children with FASDs showed promising results [48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to some of the few FASD-specific interventions (e.g. MILE program for math [55] and Children's Friendship Training for social skills, [56]), there are several novel interventions that are also being piloted, such as music training to increase attention [57]. Understanding the underlying cause of areas of weakness can also assist in targeted, clinical intervention.…”
Section: Intervention Modalities and Targetsmentioning
confidence: 99%